Interactive Media Applications as Learning Aids for Food Preservation Practice Courses for Deaf Vocational Students - Lina Mufidah; Rachmawati, Eka; Sulistyani, Titik (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This study aims to develop an interactive learning application that helps in providing direction on food preservation practices which are then expected to be a means of delivering material using video tutorials, text and equipped with sign language interpreter videos so that learning becomes more communicative for deaf students. The research method used in this study is the Research and Development (R&D) method. The development procedure used in this research is the Luther-Sutopo method. Subjects in this study focused on deaf students who took food preservation courses. The form of the instrument used in this research is a questionnaire. The results of the study show that at stage The results of the study show that at stage (1) The interactive learning application can help in providing direction on food preservation practices for deaf students. This application contains a means of delivering material in the form of learning tutorial videos equipped with text and added with translator videos using sign language. This application is declared feasible in all aspects either by media experts or deaf students. (2) The results of application trials from media experts obtained the most in the aspect of assessing media integration. The results of the trial obtained from deaf students obtained the highest score was on the artistic and aesthetic aspects and on the aspects of overall functioning.